Resolution of unilateral sensorineural hearing loss in a pediatric patient with a severe phenotype of Muckle-Wells syndrome treated with Anakinra: a case report and review of the literature - Cinzia Marchica; Faisal Zawawi; Dania Basodan; Rosie Scuccimarri; Sam J. Daniel (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Muckle-Wells syndrome (MWS) is a rare auto-inflammatory disease characterized by the presence of recurrent urticaria, deafness and amyloidosis. Progressive sensorineural hearing loss (SNHL) is reported to occur in up to 85% of patients occurring in the second and third decades and as early as the first decade in patients with a more severe phenotype, thus potentially having a significant impact on a child’s development. IL-1 inhibitors, such as Anakinra, have been described to improve systemic inflammation, and stabilize or improve hearing status as well. However, complete resolution of hearing loss has been rarely reported. The objective of this article is to highlight the clinical presentation of a pediatric patient with a severe form of MWS and report on the complete resolution of SNHL with the use of Anakinra. Case presentation A 3-year-old boy was referred to our hospital to assess for the possibility of MWS given a history of hives and recurrent episodes of fever with a family history of MWS in his mother. Of note, the patient’s history was significant for conductive hearing loss, speech delay, as well as recurrent acute otitis media episodes. Genetic analysis was performed and diagnosis of MWS was confirmed due to the presence of a NLRP3 gene mutation. Further work-up demonstrated the presence of papilledema and elevation of systemic inflammatory markers for which Canakinumab was initiated. Despite initiation of this treatment, audiogram evaluation demonstrated a new right-sided SNHL. Lumbar puncture also revealed aseptic meningitis. Canakinumab was eventually discontinued and Anakinra initiated. Within 7 months of treatment with Anakinra at 5 mg/kg sc daily, resolution of the SNHL was observed. With further escalation of the Anakinra dose, there was also complete resolution of the aseptic meningitis. Conclusions Progressive hearing loss is a significant finding in patients with MWS. Early screening as well as initiation of Anakinra can lead to complete resolution of SNHL even in a patient with a severe spectrum of MWS. However, as this case demonstrates, longer treatment duration and higher doses of Anakinra may be required to achieve this.